Temperature limits for storage of extended boar semen from the perspective of the sperm's energy status - Henning, Heiko; Nguyen, Quynh Thu; Wallner, Ulrike; Waberski, Dagmar (Frontiers in Veterinary Science, 2022)
The optimum storage temperature for liquid-preserved boar semen has been empirically determined to be between 15°C and 20°C. Lower temperatures provide an advantage to inhibit bacterial growth, but are regarded as critical due to the high sensitivity of boar spermatozoa to chilling injury. Higher storage temperatures are supposed to induce energy deficiency due to an insufficient depression of metabolic cell activity. However, experimental evidence for alterations of the sperm’s energy status in relation to storage temperature and duration is missing. Therefore, we aimed to revisit the upper and lower storage temperature limits for liquid-preserved boar semen from the perspective of the sperm’s energy metabolism. Ejaculates (n= 7 boars) were cooled down in Beltsville Thawing Solution (BTS) to 25°C, 17°C, 10°C or 5°C and stored for up to 120 h. ATP and adenylate energy charge (EC) levels were assessed at storage temperature (24 h, 72 h, and 120 h storage) and after subsequent re-warming (38°C). Sperm quality and energy status remained at a stable level in samples stored at 25°C and 17°C. Chilling to and storage at 10°C or 5°C in BTS provoked cold shock in a subset of sperm as shown by a loss in viability and motility (P<0.05), which was accompanied by a significant release of adenine nucleotides into the semen extender. Prolonged storage for 120 h resulted in significantly lower mean ATP concentrations in viable spermatozoon at 5°C or 10°C compared to 17°C (P<0.05). Cluster analysis revealed that the main sperm subpopulation, i.e., sperm with moderate speed and linearity, decreased from 50 % to 30 % (P<0.05) in favor of slow moving spermatozoa (5°C) or spermatozoa with a hyperactivation-like motility pattern (10°C). The results point to a sublethal imbalance in available ATP in a subset of the surviving sperm population, rather than a general decrease in available ATP in all spermatozoa. In conclusion, storing diluted boar semen at a stable temperature between 25°C and 15°C is a safe procedure concerning the spermatozoa’s energy status. Future concepts for boar semen preservation below 15°C require measures which ameliorate the imbalanced energy status in viable spermatozoa.